Skin barrier in rosacea - Flavia Alvim Sant'Anna Addor (Sociedade Brasileira de Dermatologia, 2016)
Abstract Recent studies about the cutaneous barrier demonstrated consistent evidence that the stratum corneum is a metabolically active structure and also has adaptive functions, may play a regulatory role in the inflammatory response with activation of keratinocytes, angiogenesis and fibroplasia, whose intensity depends primarily on the intensity the stimulus. There are few studies investigating the abnormalities of the skin barrier in rosacea, but the existing data already show that there are changes resulting from inflammation, which can generate a vicious circle caused a prolongation of flare-ups and worsening of symptoms. This article aims to gather the most relevant literature data about the characteristics and effects of the state of the skin barrier in rosacea.